Public Health Directives in a Pandemic: Paradoxical Messages for Domestic Abuse Victims in Four Countries - Holt, Stephanie; Gregory, Soma; Elliffe, Ruth (My University, 2022)
When the COVID-19 pandemic manifested urgent concerns were raised around the globe about the increased risk that public health restrictions could pose for victims of domestic abuse. Governments, NGOs and community services swiftly responded to convey the message that services for victims were operational and restrictions did not apply to those fleeing harm. This paper reports on the various approaches used to communicate this public health messaging during COVID-19, further highlighting strengths and learning which could inform future crises messaging. It utilises data gathered through a rapid review and mapping of policy and practice initiatives across 4 high-middle income countries: UK, Australia, South Africa and Ireland. Four themes were identified: (1) Top-down: National media messaging; (2) Top-down: Political leadership; (3) Traditional media vs. social media and (4) Bottom-up messaging: Localised, community-based messaging. It was found that a strong, clear top-down stance on domestic abuse was perceived as beneficial during COVID-19. However, a stronger focus on evaluation, reach and impact, particularly for minority groups may be required. Newer forms of media were shown to have potential in conveying messaging to minority groups. Community and grassroots organizations demonstrated their experiential knowledge in reaching target audiences. Harnessing this expertise for future crises messaging may be valuable.
Keywords: COVID-19; Awareness raising; Domestic abuse; National messaging; Public messaging; Domestic Violence; Domestic violence, intimate partner homicide, child welfare; Emotional-behavioural Problems; Communication; Education; Gender; Policy; Social services, interventions and supports